2005
DOI: 10.1111/j.1440-1797.2005.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin I and beta 2 microglobulin as risk factors for early‐onset atherosclerosis in patients on haemodialysis

Abstract: Besides well-known cardiovascular (CV) risk factors, cTnI and beta2M were related with C-IMT in that they may have important roles in early-onset atherosclerosis in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
2
23
1
Order By: Relevance
“…18 In patients on HD, serum b 2 M is markedly increased and predicts all-cause mortality, 19,20 but studies on the relationship between serum b 2 M and cardiovascular disease are limited. It has been reported that serum b 2 M correlates with carotid IMT 21 and the number of calcified valves. 6 Serum b 2 M indicates the clearance of middle molecules by HD, or may be related to inflammation, as suggested by some authorities.…”
Section: Discussionmentioning
confidence: 99%
“…18 In patients on HD, serum b 2 M is markedly increased and predicts all-cause mortality, 19,20 but studies on the relationship between serum b 2 M and cardiovascular disease are limited. It has been reported that serum b 2 M correlates with carotid IMT 21 and the number of calcified valves. 6 Serum b 2 M indicates the clearance of middle molecules by HD, or may be related to inflammation, as suggested by some authorities.…”
Section: Discussionmentioning
confidence: 99%
“…The mean serum cardiac troponin I level in the control group was significantly lower than it was in patients both with and without left ventricular hypertrophy. The mean serum cardiac troponin I level was significantly higher in patients with left ventricular hypertrophy than it was in those without left ventricular hypertrophy (Zumrutdal et al, 2005). The relationship between carotid artery intima-media thickness, serum cardiac troponin I levels and left ventricular hypertrophy may demonstrate that subclinical atherosclerotic changes and/or adaptation may occur along with cardiac alterations.…”
Section: Left Ventricular Hypertrophymentioning
confidence: 86%
“…Supporting that study, while no relationship between ESR and carotid artery intima-media thickness was found, a relationship in hemodialysis patients without comorbidities was found between Hctcorrected ESR and carotid artery intima-media thickness, beyond other inflammatory markers, CRP, and fibrinogen. Although larger additional studies are needed to determine the potential value of Hct-corrected ESR as an inflammatory marker for early-onset atherosclerosis, this relationship may again reflect the role of non-specific inflammation in CV risk of the 'healthy' hemodialysis patients ( Zumrutdal et al, 2005).…”
Section: Hematocrit-corrected Erythrocyte Sedimentation Rate (Hct-cormentioning
confidence: 99%
See 2 more Smart Citations